Peningkatan Hasil Jagung Manis di Lahan Kering Masam melalui Aplikasi Pupuk Organik dan Pengaturan Olah Tanah - Neni Marlina; Gusmiatun Gusmiatun; Desy Marlina (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Marlina N, Gusmiatun G, Marlina D. 2021. increased sweet corn yield in acid dry land through application of organic fertilizer and tillage settings. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimalke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 490-497. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). Acid dry land has the potential to develop sweet corn because it covers 29% of the total land area in Indonesia. The challenges faced in acid dry land are soil fertility and lumpy soil structure, therefore to increase sweet corn yields can be through the application of solid and liquid organic fertilizers and tillage settings. The purpose of the study was to determine the right type of organic fertilizer and appropriate tillage settings for sweet corn cultivation in the acid dry land. This research was conducted in 2 Prajen Hamlet, Banyuasin Regency, South Sumatra from December 2018 to March 2019. The layout in the field was arranged based on the Split Plot Design with 6 treatment combinations repeated 4 times. The main plots are tillage (O): no tillage (O0), minimum tillage (O1), and maximum tillage (O2). Sub-plots are types of Organic fertilizers (P): liquid organic fertilizer (P1) and solid organic fertilizer (P2). The results showed that minimum tillage with solid organic fertilizer was able to increase sweet corn yield by 146% when compared to treatment without tillage with liquid organic fertilizer, increasing by 120% when compared to treatment without tillage with solid organic fertilizer.